EXPERIMENTAL STUDIES REGARDING THE RISK-FREE WORK OF THE GANTRY CRANES (Journal of Engineering Studies and Research, 2015)
The present paper sets that the prerequisite of a crane’s failure (changes of the optimum technical state – risk of accidents occurrence), appear in their vibratory mark. The research has as main goal the increase of the work safety and the elimination of the risk of accidents. The tests had in view both the truss answer to dynamic forces in wind-bracings and the dynamic regime of the main beam.
Keywords: crane; work safety; risk; wind-bracing; failure; vibratory state